Upper and Lower Contra-$(τ_1,τ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions between bitopological spaces, namely upper contra-$(τ_1,τ_2)$-continuous multifunctions and lower contra-$(τ_1,τ_2)$-continuous multifunctions. Moreover, several characterizations and some properties concerning upper contra-$(τ_1,τ_2)$-continuous multifunctions and lower contra-$(τ_1,τ_2)$-continuous multifunctions are investigated.
Keywords: upper contra-$(τ_1,τ_2)$-continuous multifunction; lower contra-$(τ_1,τ_2)$-continuous multifunction